Alopecia areata: A multifactorial autoimmune condition. (March 2019) - Simakou, Teontor; Butcher, John P.; Reid, Stuart; Henriquez, Fiona L.
Abstract: Alopecia areata is an autoimmune disease that results in non-scarring hair loss, and it is clinically characterised by small patches of baldness on the scalp and/or around the body. It can later progress to total loss of scalp hair (Alopecia totalis) and/or total loss of all body hair (Alopecia universalis). The rapid rate of hair loss and disfiguration caused by the condition causes anxiety on patients and increases the risks of developing psychological and psychiatric complications. Hair loss in alopecia areata is caused by lymphocytic infiltrations around the hair follicles and IFN-γ. IgG antibodies against the hair follicle cells are also found in alopecia areata sufferers. In addition, the disease coexists with other autoimmune disorders and can come secondary to infections or inflammation. However, despite the growing knowledge about alopecia areata, the aetiology and pathophysiology of disease are not well defined. In this review we discuss various genetic and environmental factors that cause autoimmunity and describe the immune mechanisms that lead to hair loss in alopecia areata patients. Highlights: Alopecia areata is a polygenic and multifactorial autoimmune disease characterised by non-scarring hair loss. Autoreactive CD8+, CD4+, NK cells and pDCs infiltrate around the hair follicles during the growth (anagen) phase. Increased cytokine activity results in disruption of the hair follicle immune privilege and termination of the anagen phase.